Does hyponatremia pose a risk factor for hip fractures in the elderly? Can a primary physician prevent it? - R Vijay Kumar; Mayur P. Manchekar; Manoj Kashid; Surbhi Rajauria; Sanjay K. Rai (Journal of Family Medicine and Primary Care, 2023)
Objective: Fracture around the hip is amongst the most common and serious fractures in the elderly, which leads to significant morbidity and mortality. In literature, many authors noted that even mild hyponatremia adversely affects bone, leading to an increased incidence of fractures. We aim to determine whether chronic hyponatremia (>90-day duration) increases the risk of hip fracture in the elderly and whether primary care physicians can help to prevent it. Materials and Methods: During the period from January 2020 to March 2022, we identified 145 patients aged between 65 and 90 years who were admitted to the hospital with hip fractures following a fall and compared them with 140 healthy controls. We recorded sodium (Na) serum levels in all included patients at the time of arrival and consequently for 3 days and compared them with those of controls. Logistic regression was used to calculate odds ratios (ORs). We measured serum Na levels for 3 days and took the average to ascertain hyponatremia. Result: In the study, the odds of hyponatremia were 70.3% with a confidence interval of 95% versus 3.6% in controls (P = 0.05). Age and hyponatremia were strongly associated with hip fractures following a fall. With a 5-year increase in age, the univariate OR for hip fracture increased by 5.67 (P < 0.0001). After adjusting for age, cases were nearly six times more likely to be hyponatremic than controls (OR = 4.90, P = 0.04). Conclusion: In our study, we noted that even mild chronic hyponatremia in old age increased the chance of falls. Addressing hyponatremia in the elderly may reduce the risk of falls and minimize hip fractures.